Bridge maintenance 2 inspection, maintenance, assessment and repair - Harding, J. E.; Parke, G. A. R.; Ryall, M. J. (Thomas Telford, 1993)
This volume focuses on ways of limiting the whole life cost of new bridges and extending the life of old bridges by presenting preventative and curative measures which have been found in practice to work.